2012
DOI: 10.9775/kvfd.2011.5824
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Ethanol and Acetone Extract of Plantago major L. on Gram Positive and Gram Negative Bacteria

Abstract: SummaryIn this study, minimum inhibitor concentrations of acetone and ethyl alcohol extracts of Plantago major L. leaves on predetermined bacteria species was determinbed by Macrodilution liquid (tube) method. Both extracts were tested for nine bacteria species (Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, Proteus mirabilis, Salmonella enteritidis). Ethyl alcohol extract showed no antibacterial activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Several authors have mentioned P. major as an antibacterial, antifungal, and antiviral compound. A study in Turkey demonstrated that the acetone extract of P. major has antimicrobial properties against nine species of bacteria, and also, an ethyl alcohol extract has bactericidal activity against E. coli and Bacillus cereus [24]. Fungicidal activity of P. major against growth, metabolic activity, and biofilm formation of Candida albicans was proved in a study by Shirley et al [25].…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have mentioned P. major as an antibacterial, antifungal, and antiviral compound. A study in Turkey demonstrated that the acetone extract of P. major has antimicrobial properties against nine species of bacteria, and also, an ethyl alcohol extract has bactericidal activity against E. coli and Bacillus cereus [24]. Fungicidal activity of P. major against growth, metabolic activity, and biofilm formation of Candida albicans was proved in a study by Shirley et al [25].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the highest antimicrobial activity of Rumex acetosa L. against all strains had a significant effect against Salmonella enteritidis compared to the other extracts, while the highest antimicrobial activity of Urtica dioca L. was recorded against L. innocua, with each plant demonstrating relatively lower but fairly significant activity against the other strains. The antimicrobial properties of Rumex acetosa L. against staphylococci and Gramnegative bacteria, including Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, as well as fungi Candida spp., or Trichophyton mentagrophytes, have been reported using the agar dilution method [35]. Urtica dioca L. has also demonstrated antimicrobial activity against Acinetobacter calcoaceticus, Bacillus cereus, Bacillus spizizenii, Micrococcus spp., Vibrio parahaemolyticus, Escherichia coli, Bacillus subtilis, methicillin-resistant Staphylococcus aureus, Klebsiella pneumonia, and Salmonella paratyphi B [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Acetone extract performed well when used against Bacillus cereus (3.562 mg/mL), while performing poorly when used against B. subtilis, P. mirabilis, P. aeruginosa, and S. epidermidis (28.500 mg/mL) [65]. However, investigations by Metiner et al (2012) showed that all the bacteria utilized in the study-aside from E. coli and B. cereus-are resistant to the ethanol extract of Plantago major's roots [66]. At the same time, two strains of Porphyromonas gingivalis and Fusobacterium nucleatum in vitro were inhibited by ethanol extracts of the root of Plantago major at doses of 75% and 100%.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%